2021
DOI: 10.1101/2021.09.20.461153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple stressors and recruitment failure of long-lived endangered freshwater mussels with a complex life cycle

Abstract: Multiple stressors can interactively affect the population of organisms; however, the process by which they affect recruitment efficiency remains unclear for empirical populations. Recruitment efficiency can be regulated at multiple stages of life, particularly in organisms with complex life cycles. Understanding the interactive effects of multiple stressors on recruitment efficiency and determining the bottleneck life stages is imperative for species conservation. The proportion of <20-year-old juveniles o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Under such conditions, a chain of adult abundance decreases in winter, high mortality of gravid mussels and newly born juveniles occurs in summer, and population size decreases with a lack of juveniles at annual or longer timescales. Recent studies have indicated that multiple stressors can limit the community structure, distribution, and reproduction of freshwater species, including freshwater mussels, in complex ways (Birk et al, 2020;Miura et al, 2023a). Our findings extend the multiple-factor paradigm and underscore the importance of considering survival limitation factors acting at multiple life stages of freshwater mussels at different times of the year.…”
Section: Implications For Conservationsupporting
confidence: 71%
See 1 more Smart Citation
“…Under such conditions, a chain of adult abundance decreases in winter, high mortality of gravid mussels and newly born juveniles occurs in summer, and population size decreases with a lack of juveniles at annual or longer timescales. Recent studies have indicated that multiple stressors can limit the community structure, distribution, and reproduction of freshwater species, including freshwater mussels, in complex ways (Birk et al, 2020;Miura et al, 2023a). Our findings extend the multiple-factor paradigm and underscore the importance of considering survival limitation factors acting at multiple life stages of freshwater mussels at different times of the year.…”
Section: Implications For Conservationsupporting
confidence: 71%
“…One of the most prevalent signs of population decline in freshwater mussels is the cessation of their reproduction, which can often be reflected in disproportionately fewer juveniles in population demography and small population sizes (i.e., abundance) (Österling et al, 2010;Negishi & Kayaba, 2010). Efforts have been made to identify how population decline and reproduction cessation occur by examining single or multiple life-history stages of species in relation to various external environmental factors (Geist et al, 2006;Österling et al, 2010;Strayer & Malcom, 2012;Tremblay et al, 2016;Brian et al, 2021;Miura et al, 2023a). Furthermore, as intrinsic properties of mussels, demographics, including size frequency, age structure, sex ratios, and survival rates, are among the key parameters in inferring impaired populations and projecting how and whether the populations would change in the future (Ferreira-Rodríguez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the next step, other limiting factors of M. laevis recruitment and their relative importance should be determined in detail to recover M. laevis recruitment more effectively. In particular, the post-parasitic juvenile stage could also be a bottleneck for freshwater mussel recruitment together with the parasitic stage (Miura et al 2021a). Evaluating the performance of this stage and its bottleneck factors is especially important for improving M. laevis recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Margaritifera kurilensis (Zatravkin & Starobogatov, 1984) also occurred at study sites (Miura et al, 2019b). Margaritifera kurilensis has a different reproductive season (March to May) and suitable host-fish species (white-spotted char Salvelinus leucomaenis leucomaenis (Pallas, 1814) and perhaps Dolly Varden char S. malma krascheninnikovi Taranetz, 1933) with M. laevis (Kobayashi and Kondo 2009;Miura et al 2021a).…”
Section: Study Sitementioning
confidence: 96%